Publishing Brand and Its Communication Potential - T. G. Kupriyanova (Библиосфера, 2023)
In the context of a decline in publishing circulation, there is a need to activate existing methods and ways to correct negative trends. Traditional in overcoming the crisis is the introduction of progressive forms and methods of book trade, but the development of business processes on online platforms leveled the importance of bookselling enterprises and led to a reduction in the bookselling network. However, the online book trade at this stage has not reached the required level of monetization and did not live up to expectations of management. The purpose of this material is to comprehend the publishing brand as a holistic concept, which includes not just a complex of such elements as the author’s name, title of the work, genre, but as a combination of the brand of the author’s name (author’s brand), the brand of the title of the work (brand naming), the brand of the genre of the work. Among the tasks to identify the problem of the impact of a branded publishing product on the consumer of fiction, children’s literature; definition of a publishing brand as a marketing strategy tool for a modern publishing house. The article discusses the role of the publishing brand in the market business model, the main elements of the publishing brand, the degree of influence on consumer activity, as well as the impact of digital technologies on the creation of a cross-media product on Internet platforms.